2012
DOI: 10.1371/journal.pone.0036644
|View full text |Cite|
|
Sign up to set email alerts
|

Is a Genome a Codeword of an Error-Correcting Code?

Abstract: Since a genome is a discrete sequence, the elements of which belong to a set of four letters, the question as to whether or not there is an error-correcting code underlying DNA sequences is unavoidable. The most common approach to answering this question is to propose a methodology to verify the existence of such a code. However, none of the methodologies proposed so far, although quite clever, has achieved that goal. In a recent work, we showed that DNA sequences can be identified as codewords in a class of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 15 publications
0
13
0
3
Order By: Relevance
“…One of the simplest error detection and correction codes is the Hamming code such as the Hamming (7.4) code which can correct a single-bit error but detect one-bit and two-bit errors. It has been suggested that exon-intron genes are Hamming codewords (Faria et al, 2012). There are two main types of EDAC other than turbo codes -block codes and convolutional codes.…”
Section: Denial Of Evolutionary Capacitymentioning
confidence: 99%
“…One of the simplest error detection and correction codes is the Hamming code such as the Hamming (7.4) code which can correct a single-bit error but detect one-bit and two-bit errors. It has been suggested that exon-intron genes are Hamming codewords (Faria et al, 2012). There are two main types of EDAC other than turbo codes -block codes and convolutional codes.…”
Section: Denial Of Evolutionary Capacitymentioning
confidence: 99%
“…The significance of this can be demonstrated as follows. In [8], Faria et al work on the ring Z 4 and they find a codeword that corresponds to a part of real DNA with one error. But, in doing so they do not fix a correspondence between elements of Z 4 and the DNA nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…O gene Hint-1 do nematoide C. elegans (identificado por "geneID"número 184760, no NCBI)é composto por 3éxons e 2íntrons com os seguintes comprimentos (em termos de nucleotídeos):éxon 1 com 123,íntron 1 com 44,éxon 2 com 138,íntron 2 com 74 eéxon 3 com 132, totalizando 511 nucleotídeos. Este gene foi identificado como uma palavra-código de um código BCH com parâmetros (511, 502, 3) sobre o anel Z 4 com polinômio gerador g(x) = x 9 + 2x 7 + x 5 + 3, via o algoritmo de geração de sequências de DNA proposto em [3]- [5]. A matriz geradora G tem dimensão 502 × 511.…”
Section: Introductionunclassified